2019
DOI: 10.1088/1367-2630/ab3508
|View full text |Cite
|
Sign up to set email alerts
|

Entangling two magnon modes via magnetostrictive interaction

Abstract: We present a scheme to entangle two magnon modes in a cavity magnomechanical system. The two magnon modes are embodied by collective motions of a large number of spins in two macroscopic ferrimagnets, and couple to a single microwave cavity mode via magnetic dipole interaction. We show that by activating the nonlinear magnetostrictive interaction in one ferrimagnet, realized by driving the magnon mode with a strong red-detuned microwave field, the two magnon modes can be prepared in an entangled state. The ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(71 citation statements)
references
References 62 publications
1
70
0
Order By: Relevance
“…In analogy to cavity optomechanics, in recent years cavity magnomechanics (CMM) [14] has received increasing attention, owing to its potential for realizing quantum states at a more macroscopic scale [15][16][17] and possible applications in quantum information processing and quantum sensing [18]. In these systems, a magnon mode (spin wave) of a ferromagnetic yttrium-iron-garnet (YIG) sphere couples to a microwave (MW) cavity field [19][20][21][22][23][24], and simultaneously couples to the vibrational phonon mode (deformation mode) of the sphere via the magnetostrictive force [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In analogy to cavity optomechanics, in recent years cavity magnomechanics (CMM) [14] has received increasing attention, owing to its potential for realizing quantum states at a more macroscopic scale [15][16][17] and possible applications in quantum information processing and quantum sensing [18]. In these systems, a magnon mode (spin wave) of a ferromagnetic yttrium-iron-garnet (YIG) sphere couples to a microwave (MW) cavity field [19][20][21][22][23][24], and simultaneously couples to the vibrational phonon mode (deformation mode) of the sphere via the magnetostrictive force [25].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum effects in CMM have been first studied in reference [15], which shows the possibility of creating genuine tripartite magnon-photon-phonon entanglement and cooling of the mechanical motion. Furthermore, proposals have been made for generating squeezed vacuum states of magnons and phonons [16], and entangled states of two magnon modes in CMM [17]. Quite recently, CMM has been used to produce stationary entangled MW fields by coupling a magnon mode to two MW cavities [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavity magnomechanical systems, in parallel with cavity optomechanical systems [13], represent a promising platform for studying macroscopic quantum phenomena [14,15], since the YIG sphere is around hundreds of micrometers in diameter, at the macroscopic scale. More interestingly, recent studies have already shown that quantum effects, such as quadrature squeezing, entanglement, and magnon quantum blockade, can be generated in cavity magnomechanics [16][17][18][19]. These findings inspire us to further explore novel quantum phenomena in the hybrid macroscopic quantum interface of photons, magnons, and phonons.…”
Section: Introductionmentioning
confidence: 96%
“…We thus focus on the controllability of pathway interferences through the phase difference between the cavity-probe tone and the magnon-pump tone, which is introduced by the coupling loops' technology [61][62][63][64]. The direct magnon pump is becoming useful in realizing the light-wave interface [46][47][48], enhancing the Kerr nonlinearity [65][66][67], and has also been adopted to observe the magnetostrictioninduced quantum entanglement [68][69][70][71][72], among other applications.…”
Section: Introductionmentioning
confidence: 99%